Influences of the culture of science on nursing knowledge development: Using conceptual frameworks as nursing philosophy in critical care nursing. (9th July 2020) - Burns, Margie; Bally, Jill; Burles, Meridith; Holtslander, Lorraine; Peacock, Shelley
Abstract: Nursing knowledge development and application are influenced by numerous factors within the context of science and practice. The prevailing culture of science along with an evolving context of increasingly technological environments and rationalization within health care impacts both the generation of nursing knowledge and the practice of nursing. The effects of the culture of science and the context of nursing practice may negatively impact the structure and application of nursing knowledge, how nurses practice, and how nurses understand the patients and families for whom they care. Specifically, the nature of critical care and its highly technical environment make critical care nursing especially vulnerable to these potentially negative influences. The influences of the culture of science and the increasingly technical practice context may result in an overreliance on the natural sciences to guide critical care nursing actions and an associated marginalization of the caring relationship in critical care nursing practice. Within this environment, nursing philosophy may not be foundational to nursing actions; rather, the dominant culture of science and the rationalization of health care may be informing nursing practice. As such, the ideology and goals of nursing may not be central to the practice of critical care nursing. The purpose of this paper is to explore the influence of the culture of science on the development of nursing knowledge and theory. Further, we aim to describe the value of using conceptual frameworks, such as Roy's Adaptation Model, as a nursing philosophy to influence the development of person‐centred nursing knowledge and theory to inform critical care nursing practice as it related to the care of patients and families. In doing so, nursing philosophy is situated as foundational for nursing actions.